The Problematic of The Lexicographic Definition of Lexical Combinations in Al-Muğam Al-Wasīṭ - Bilal Shbani, Bana; Abdul Aziz Mehrez , Nada (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
Lexical Combinations are an important part of the linguistic balance in any language, which contributes to the disclosure of beauty, accuracy and the harmony of words. According to the role played by this syntactic phenomenon enriching the lexicographic definitions, the lexicon is carefully codifying them in order to incorporate the lexical entry into the spoken or written discourse indicating how it is used in this or that sense. It sometimes appears in the lexicon as an integral part of the definition, other times as primary or secondary entries. However, they vary in ambiguity and clarity according to their patterns and context. Building on that, this study addresses the Lexicographic definition of Lexical Combinations in their different types and takes Al-Muğam Al-Wasīṭ of the Arabic language Academy in Cairo as an applicable example. The study shows the techniques used by Al-Wasīṭ in clarifying the implications of its Lexical Combinations and its suitability to their nature. Moreover, this work also focuses on studying two other aspects related to the issue of Lexicographic definition, which are determining the functional domain, and etymology of Lexical Combinations in this dictionary.